Lightweight Strategic Path for Digital Transformation in Small and Medium Enterprises — A Solution Based on Management Consulting Practice - Zhu, Chongguang (European Journal of AI, Computing & Informatics, 2025)
As global economic digitalization accelerates, small and medium-sized enterprises (SMEs) play a critical role in the U.S. economy. However, due to limited budgets, insufficient technical capabilities, and a lack of management experience, SMEs face significant challenges in digital transformation. This paper focuses on the digital pain points of SMEs and proposes a "lightweight" strategic approach, which emphasizes low-cost, easy-to-implement, and stepwise digital solutions to enhance operational efficiency. Drawing on management consulting practices, the study designs actionable digital transformation solutions encompassing tool selection, phased implementation, budget and resource allocation, and risk management. Case analyses demonstrate the effectiveness of the lightweight strategy in improving operational efficiency, reducing transformation risks, and optimizing resource utilization. Furthermore, the paper highlights the value of management consultants in facilitating SME digitalization. The findings provide practical guidance for SMEs in the U.S. and offer strategic insights for future digital development.